La recreación en el proceso enseñanza aprendizaje en los niños de segundo año de Educación Básica en la Unidad Educativa "Jorge Icaza". - Pullupaxi Alvarez, Liliana Elizabeth (2021)
Recreational time is a space for recreation; therefore, this research investigates how recreational activities influence the learning process in second-year children. The objective of this research is to determine the influence of recreation in the teaching learning process through the application of appropriate methodological strategies for boys and girls in the second year of GBS. The designed methodology was qualitative and quantitative, it is a cross-sectional study; The population was made up of teachers, the Principal of the unit and 34 students who belong to the second year of Basic Education. The instruments used were surveys and an observation sheet. The results of the diagnosis indicate that in the institution only some teachers include recreational activities in their planning, most of teachers consider the benefits of children's recreation important, on the other hand, the observation sheet for children indicates that more than half of the Recreational activities are spontaneous and few directed activities. With the application of the proposal, it is observed that both recreational activities promote playful distraction, and at the same time attention and concentration on the Teaching-Learning Process and promote meaningful learning through student motivation.